Recursos didácticos innovadores para fortalecer las estrategias de enseñanza en las instituciones de Educación Básica Superior del Distrito 12D05 Palenque - Vinces en la Provincia de Los Ríos - Montiel Morán, Elena Magalys (2022)
The research is developed by the need to strengthen teaching-learning strategies, where innovative didactic resources play a predominant role because they are tools that promote basic, disciplinary, pedagogical and didactic skills, conducive to promoting school learning towards integral development and diverse of students at different levels and contexts of life. The research takes place in the Educational District 12D05 belonging to the province of Los Ríos, and in its study population, teachers of basic higher education in rural areas are considered. The study is qualitative-quantitative, not experimental, and due to its temporality, it is retro-prospective. The research results showed several factors that affect the effectiveness of the teaching strategies implemented by teachers, such as the excessive use of standardized instruments in pedagogical practices, presents, the deficit of pedagogical innovation in the didactic design, the virtual learning environments, the little interaction between teachers, which does not allow them to have a good motivation in their pedagogical practices, the lack of a positive attitude on the part of the teachers when using the teaching strategies . In the same way, an intrinsic relationship between innovative teaching resources and teaching strategies implemented by teachers of the institutions of Higher Basic Education of District 12D05 Palenque - Vinces is evidenced.